Innovative Online Learning Media During the Covid-19 Pandemic - Palupi, Shinta; Gunawan, Gunawan; Hardi, Richki (Universitas Malikussaleh, 2023)
To improve the quality of the learning program, an efficient and effective approach in the teaching and learning process is required. Currently, educational strategies have become an essential process to enhance students' intelligence during this pandemic. In the field of education, the development of technology and communication requires training and learning using various methods. This approach involves training and teaching activities that are not limited by time and place, as they can be accessed and processed anytime and anywhere. This process aligns with the policy of the Ministry of Education and Culture of Indonesia in overcoming the challenges of learning during the Covid-19 pandemic. In the field of education, the common problem faced is the lack of effectiveness in learning. The methods of delivering materials used are not fully effective in utilizing learning resources. Additionally, suboptimal teaching schedules also affect the students' absorption of the material. Therefore, it is important to implement an approach that combines theory and practice through community service. By doing so, the results of this training will produce innovation in online learning using relevant tools, and enhance teachers' ability to implement self-directed learning approaches.